Proceedings from the Scientific Closing Seminar of the Project: Immunohistochemical, histochemical and endoscopic analysis of the bone tissue associated with peri implantitis: Development of an in vivo and in vitro model. - Beltrán, Victor; Venegas, Bernardo; Manzanares-Céspedes, María (Journal of Oral Research, 2020)
.